APPLICATION OF HALANAY INEQUALITY TO THE ESTABLISHMENT OF THE EXPONENTIAL STABILITY OF DELAYED COMPARTMENTAL SYSTEM - ., Sariyasa (IndoMS, 2007)
The dynamical convergence of a compartmental system with transport delays is studied. An easily verifiable delay independent sufficient condition for the system to be globally exponentially stable is obtained. Halanay differential inequality is employed to establish the global exponential stability.DOI :Â http://dx.doi.org/10.22342/jims.13.2.67.191-196